2021
DOI: 10.1242/dev.199559
|View full text |Cite
|
Sign up to set email alerts
|

The molecular complex of ciliary and golgin protein is critical for skull development

Abstract: Intramembranous ossification, which consists of direct conversion of mesenchymal cells to osteoblasts, is a characteristic process in skull development. One critical role of these osteoblasts is to secrete collagen-containing bone matrix. However, it remains unclear how the dynamics of collagen trafficking is regulated during skull development. Here, we reveal the regulatory mechanisms of ciliary and golgin proteins required for intramembranous ossification. During normal skull formation, osteoblasts residing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…We have recently reported that proliferation and differentiation activities in CNC-derived osteoblasts are normal in Trip11 cKO mice. 11 This suggests that the initial process of osteogenesis may not be affected by deletion of Trip11. However, it remains unclear whether disruption of Trip11 affects cell survival and thus causes craniofacial skeletal defects.…”
Section: Loss Of Trip11 Increases Apoptosis In Skull Tissuesmentioning
confidence: 98%
See 4 more Smart Citations
“…We have recently reported that proliferation and differentiation activities in CNC-derived osteoblasts are normal in Trip11 cKO mice. 11 This suggests that the initial process of osteogenesis may not be affected by deletion of Trip11. However, it remains unclear whether disruption of Trip11 affects cell survival and thus causes craniofacial skeletal defects.…”
Section: Loss Of Trip11 Increases Apoptosis In Skull Tissuesmentioning
confidence: 98%
“…As we have recently reported, GMAP210 is critical for regulating collagen trafficking in the area of the osteogenic front (OF). 11 In addition to this unique function, GMAP210 is also required for osteoblast cell survival via orchestrating both ER and Golgi stress. Therefore, loss of Trip11 in CNC-derived osteoblasts may result in both less collagen secretion and increased cell death, leading to skull defects in mice (Figure 8).…”
Section: Loss Of Trip11 Is Associated With Aberrant Golgi Stress Duri...mentioning
confidence: 99%
See 3 more Smart Citations